2017
DOI: 10.1016/j.rmed.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of weight loss induced by bariatric surgery on asthma control and health related quality of life in asthmatic patients with severe obesity: A pilot study

Abstract: In severe obese asthmatic patients, the significant improvement of asthma control test and HRQoL, observed one year after LAGB, persists five years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Improvement was seen in all five components of the score, whereas the ACT score was unchanged in the control group who had no change in their weight. Similar improvements in ACT and Mini Asthma Quality of Life Questionnaire (mini-AQLQ) were reported in another study and persisted after 5 years [22]. O'BRIEN et al [25] used the Asthma Severity Score to assess 33 asthmatic patients before and after laparoscopic placement of an adjustable gastric band and found that the score decreased from 44.5 before operation to 14.3 at follow-up (p<0.001).…”
Section: Bariatric Surgery and Asthma Controlsupporting
confidence: 55%
See 1 more Smart Citation
“…Improvement was seen in all five components of the score, whereas the ACT score was unchanged in the control group who had no change in their weight. Similar improvements in ACT and Mini Asthma Quality of Life Questionnaire (mini-AQLQ) were reported in another study and persisted after 5 years [22]. O'BRIEN et al [25] used the Asthma Severity Score to assess 33 asthmatic patients before and after laparoscopic placement of an adjustable gastric band and found that the score decreased from 44.5 before operation to 14.3 at follow-up (p<0.001).…”
Section: Bariatric Surgery and Asthma Controlsupporting
confidence: 55%
“…Few studies have evaluated the effects of bariatric surgery on spirometry parameters in asthma [18][19][20][21][22]. BOULET et al [18] reported improvement in FEV1, FVC, expiratory reserve volume, functional residual capacity (FRC) and FRC/total lung capacity (TLC) in 12 asthmatic patients 1 year after surgery; none of these patients had obstruction at baseline (defined as FEV1/FVC <70%) and only two patients had FEV1 <80% of predicted value at baseline.…”
Section: Bariatric Surgery and Lung Functionmentioning
confidence: 99%
“…However, in another study, the improved effect on AHR was only found in the group of obese asthmatics with high serum (IgE) levels [187]. The effect on asthma control, therapeutic reduction, and lung function seems to persist after five years of bariatric surgery [190].…”
Section: Effects Of Weight Loss On Asthma and Inflammationmentioning
confidence: 93%
“…There is a clear need for more studies that consider the effect of a restrictive diet before surgery if one was employed. Finally, despite growing evidence that bariatric surgery could be beneficial for patients with asthma (7,9,92,93), to the best of our knowledge, no study has explored whether the airway/lung microbiome changes after bariatric surgery.…”
Section: Microbiomes and Bariatric Surgerymentioning
confidence: 99%